1997
DOI: 10.1002/art.1780400520
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence of high DNA binding activity of transcription factor AP‐1 in rheumatoid arthritis synovium

Abstract: Objective. To investigate the possible activation of transcription factor AP‐1 in rheumatoid arthritis (RA) and its involvement in the pathogenesis of RA. Methods. Synovial tissues and peripheral blood samples were obtained from 25 patients with RA and 5 patients with osteoarthritis (OA) during arthroplasty and synovectomy. The synovial tissue was digested with collagenase and separated into adherent and nonadherent cells by plastic‐adhesion methods. Nuclear extracts obtained from each sample were examined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
1
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 20 publications
1
59
1
1
Order By: Relevance
“…It is surprising that only c-Fos did not correlate with other genes, since its pattern is supposed to be similar to that of NF-κB and IKK (Trabandt et al, 1992;Asahara et al, 1997;Shiozawa et al, 1997;Firestein, 2004;Onda et al, 2004). It is possible that some DMARDs showed a greater influence on the regulation of c-Fos than of other genes.…”
Section: Discussionmentioning
confidence: 97%
“…It is surprising that only c-Fos did not correlate with other genes, since its pattern is supposed to be similar to that of NF-κB and IKK (Trabandt et al, 1992;Asahara et al, 1997;Shiozawa et al, 1997;Firestein, 2004;Onda et al, 2004). It is possible that some DMARDs showed a greater influence on the regulation of c-Fos than of other genes.…”
Section: Discussionmentioning
confidence: 97%
“…Their expression has been associated with a proliferative role in many tissues (21,33). It has been reported that c-fos and ets-2 expression was higher in rheumatoid synovial tissue than that in normal synovial tissue, suggesting that they may play an important role in the progression of RA (22,34,35). The nuclear oncogene c-fos and its product c-Fos bind to activator protein 1 666 KAWABATA ET AL sites on matrix-degrading genes, such as MMP3 and MMP9.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, JNK activation of AP-1 may be essential for promoting proinflammatory molecule production. Furthermore, cFos and c-Jun expression correlates with synovial hyperplasia in RA synovial tissue (62), and increased AP-1 DNA-binding activity is observed in RA compared with OA synovial tissue (63,64). Addition of AP-1 oligonucleotides ameliorates joint destruction in experimental arthritis models (42).…”
Section: Discussionmentioning
confidence: 99%